1982
DOI: 10.1139/v82-075
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of substituted benzothiazoles 4. Nickel(II) complexes of the bidentate benzothiazoles 1,2-bis(2-benzothiazolyl)benzene and 1,2-bis(2-benzothiazolyl)ethane

Abstract: Can. J. Chem. 68,514 (1982).The nickel coordination chemi5try of two potentially bidentate his-benzothiazole ligands is compared. 1.2-Bis(2-benzothiazoly1)-benzene (OBT), which has an o-phenylene bridge, forms square planar derivatives with Nix, (X = I, CIO,, BF,), octahedral derivatives with Nix, (X = NCS, NO,), and five-coordinate derivatives with Nix2 (X = CI, Br). 1,2-Bis(2-benzothiazoly1)ethane (BBTE), which has an ethylene bridge, forms tetrahedral derivatives with Nix, (X = C1, Br, I) and an octahedral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…5 The far-IR spectra of the chloro complexes displayed peaks due to terminal  M-Cl and  M-N (M = Co, Ni or Cu) around 315 and 278 cm -1 respectively. 14 The room temperature magnetic moments of the complexes indicate the paramagnetic nature of the metal ions except for [Ni(L) 2 ](ClO 4 ) 2 .H 2 O which behaved as diamagnetic. 5 The magnetic moments of the halo complexes of Co(II) are in the range 4.0 -4.7 BM.…”
Section: Resultsmentioning
confidence: 95%
“…5 The far-IR spectra of the chloro complexes displayed peaks due to terminal  M-Cl and  M-N (M = Co, Ni or Cu) around 315 and 278 cm -1 respectively. 14 The room temperature magnetic moments of the complexes indicate the paramagnetic nature of the metal ions except for [Ni(L) 2 ](ClO 4 ) 2 .H 2 O which behaved as diamagnetic. 5 The magnetic moments of the halo complexes of Co(II) are in the range 4.0 -4.7 BM.…”
Section: Resultsmentioning
confidence: 95%
“…The bands appearing at 468 (benzene), 462 (CH 3 Cl) and 575 nm (DMF) were due to d-d transitions. The d-d bands in the 480-460 nm region, which were assigned to 1 A 2g ← 1 A 1g , are characteristic of a Ni(II) ion in a square planar environment, [3] and the band at 575 nm, which was assigned to 3 T 1 (F) ← 3 A 2g , is characteristic of a Ni(II) ion in an octahedral environment [3,28,29]. These results indicate the coordination of two molecules of DMF to the Ni 2+ ion in Ni(H 2 BPz) 2 .…”
Section: Co(h 2 Bpz 2 )mentioning
confidence: 99%
“…A review of the literature revealed that 1,2-bis(2-benzothiazolyl)benzene and 1,2-bis(2-benzothiazolyl)ethane are frequently used as ligands and a considerable number of their complexes with late transition metals are reported [1][2][3][4][5][6] . Also, the nickel(II), cobalt(II) and copper(II) coordination chemistry of some tetradentate ligands involving benzothiazole functional groups has been published 7 .…”
Section: Introductionmentioning
confidence: 99%